Platelet mass index in very preterm infants: can it be used as a parameter for neonatal morbidities?. (1st October 2016) - Okur, Nilufer; Buyuktiryaki, Mehmet; Uras, Nurdan; Oncel, Mehmet Yekta; Ertekin, Omer; Canpolat, Fuat Emre; Oguz, Serife Suna
Abstract: Objective : Platelet mass index (PMI) is related to the platelet functionality. The aim of this study was to evaluate the correlation between PMI and the occurrence of various inflammation-related morbidities of prematurity, such as bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC), retinopathy of prematurity (ROP), intraventricular hemorrhage (IVH) and sepsis in very low-birth weight (VLBW) infants. Methods : This retrospective analysis of VLBW infants admitted to a level 3 neonatal intensive care unit from October 2012 and 2014, n  = 330. Platelet mass was calculated and recorded on the day of birth and between 3 and 7 days (second measure) for each patient. Statistical analysis included analysis of paired samples t test and independent samples t test. Result : Among VLBW neonates, PMI values were lower in infants with ROP ( p  = 0.016), BPD ( p  = 0.002), IVH ( p  = 0.018) and NEC ( p  = 0.011) when compared with the control group in the second measurement. Conclusions : In this study, we found that premature infants with BPD, NEC, ROP, IVH and sepsis had lower PMI levels in early postnatal life than infants without these diseases. This might be associated with the inflammatory process.